Polemik Kebijakan Transportasi Online - Agnes Cellyana Nainggolan; Imam Sopwan; Nurul Auliah; Ni’matullah Ni’matullah; Adien Hasanuddin (Universitas Serang Raya, 2020)
Nowadays, online transportation becomes a public need, especially for people who live in some big cities. But this phenomenon doesn’t come with any public policy about online transportation. There is still a contradiction among public policies about transportation that makes the companies of online transportation formulate their own policies which provoke conflicts. Methods used for this research is qualitative-descriptive methods. Researchers tried to explain phenomena and polemic happened by the lack of clear policy of online transportation.